Wagner – Weimar – Eisenach : Richard Wagner im Spannungsfeld von Kultur und Politik - Geyer, Helen; Georgiev, Kiril; Alschner, Stefan (2020)
Significantly, the ’Big Bang’ in reception history of Richard Wagner’s work took place in a place that was torn between the province and the residence, tradition and progress, idea and realization: in the Grand Duchy of Saxony-Weimar-Eisenach. Here Franz Liszt's future-oriented work and the legacy of the Weimar Classic combined under the reign of an ambitious Weimar court to a not unproblematic synthesis, the consequences of which did not leave Wagner unaffected. The contributions of the volume examine these interactions between culture and politics.